Single-dose, live-attenuated Japanese encephalitis vaccine in children aged 12–18 months: Randomized, controlled phase 3 immunogenicity and safety trial - Emmanuel Feroldi; Chitsanu Pancharoen; Pope Kosalaraksa; Veerachai Watanaveeradej; Kerdpanich Phirangkul; Maria R. Capeding; Mark Boaz; Sophia Gailhardou; Alain Bouckenooghe (Human Vaccines & Immunotherapeutics)
This trial in 1200 JE-vaccination naïve children (age 12–18 mo) in Thailand and the Philippines aimed to demonstrate consistency of three successive industrial scale manufacturing lots of live attenuated Japanese encephalitis chimeric virus vaccine (JE-CV) and consistency between industrial scale manufacturing lots and a fourth, development lot. Children received JE-CV from one of three successive industrial scale lots produced in Thailand (n = 899), or from a fourth development lot produced in the USA (n = 199), or hepatitis A control vaccine (n = 102). Antibodies were assessed by 50% plaque reduction neutralization test (PRNT50) at screening and Day 28. Seroconversion rates (titer of < 10 at baseline and ≥ 10 on Day 28, or a four-fold rise from a baseline titer of ≥ 10) were determined per group. Lot-to-lot consistency of seroconversion rate and GMT was demonstrated between the 3 industrial scale lots, and between these lots and the US lot. Seroconversion rate on pooled data 28 d after JE-CV vaccination (Thai lots) was 95.0% [95% confidence interval (CI); 93.3–96.3]. The safety profile of JE-CV was favorable and comparable with hepatitis A vaccine. There were no serious adverse events related to vaccination. This study demonstrated the consistency of three successive industrial scale JE-CV vaccine lots, as well as consistency with a development lot. The study also demonstrated that a single dose of JE-CV is well tolerated and elicits a high protective immune response, seroconverting 95% of JE-naïve Asian children aged 12–18 mo.   ClinicalTrials.gov: NCT00735644